RESIDUAL STRENGTH EVALUATION OF COMPOSITE LAMINATES REPAIRED BY RIVETED METAL PATCH - ZHANG AYing; XU HongMing; CHEN Hao (Jixie qiangdu)
Fastened joint repair is a main repair method for composite structure with advantages of easy disassembling,high load transferring capacity. It is important to evaluate the residual strength in repair design process. In this paper,the tensile load bearing capacity of metal riveted repair laminates were evaluated by numerical simulation using progressive failure analysis method. Laminate was modeled using shell element whereas the fasteners were modeled by beam elements. MPC technique was adopt to simulate the constraint between fastener and hole. The USDFLD subroutine was used to degrade material stiffness by multi-lever manner while damage occurred. The failure analysis results including failure mode,failure load are in good agreement with test results. The errors of predicted failure loads are with 6%,which shows the proposed method is helpful to composite fastened joint repair design.